2008
DOI: 10.5194/angeo-26-2725-2008
|View full text |Cite
|
Sign up to set email alerts
|

First mesospheric turbulence study using coordinated rocket and MST radar measurements over Indian low latitude region

Abstract: Abstract.A campaign to study turbulence in the mesosphere, over low latitudes in India, using rocket-borne measurements and Indian MST radar, was conducted during July 2004. A rocket-borne Langmuir probe detected a spectrum of electron density irregularities, with scale sizes in the range of about 1 m to 1 km, in 67.5-78.0 km and 84-89 km altitude regions over a low latitude station Sriharikota (13.6 • N, 80.2 • E). A rocket-borne chaff experiment measured zonal and meridional winds about 30 min after the Lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 30 publications
7
23
0
Order By: Relevance
“…Importantly, the spectra of the mesospheric echoes observed in this experiment would experience less shear broadening and broadening due to possible vertical wind variation over the altitude range, compared to previous LLME observations with the Gadanki radar, where the altitude resolution was 2.4 km (e.g. Kumar et al, 2007;Chandra et al, 2008). Thus, such experimental arrangements allow for the elimination of non-turbulent contributions to the spectral width and, finally, correct evaluation of the parameters of turbulence.…”
Section: Experimental Settingsmentioning
confidence: 84%
See 2 more Smart Citations
“…Importantly, the spectra of the mesospheric echoes observed in this experiment would experience less shear broadening and broadening due to possible vertical wind variation over the altitude range, compared to previous LLME observations with the Gadanki radar, where the altitude resolution was 2.4 km (e.g. Kumar et al, 2007;Chandra et al, 2008). Thus, such experimental arrangements allow for the elimination of non-turbulent contributions to the spectral width and, finally, correct evaluation of the parameters of turbulence.…”
Section: Experimental Settingsmentioning
confidence: 84%
“…If interpreted as turbulent echoes, they correspond to 20-200 mW kg −1 turbulent energy dissipation rates. Chandra et al (2008) and Uma Das et al (2009) reported energy dissipation rates of 1-100 mW kg −1 for the same altitude range, which were derived from the rocket measurements from Sriharikota located about 100 east of Gadanki. The LLME spectral widths for our three cases are close to those (2-3 m s −1 ) measured by Chandra et al (2008) with the same radar in July 2004.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our measurements, system noise, from laser mode instability and photon shot noise, becomes dominant at frequencies above a few Hz. Rocket measurements (Chandra et al 2008) indicate that the inner scale of turbulence in the mesosphere is of order 10 m. With a typical average wind speed of ∼30 ms −1 , we would thus expect the PSD to turn down above a few Hz. In any case, the power law is not expected to continue much above ∼30 Hz.…”
Section: Discussionmentioning
confidence: 99%
“…A study of neutral turbulence generated irregularities was made by Chandra et al (2008) and Patra et al (2009) through simultaneous rocket, radar and ionosonde measurements from Sriharikota and Gadanki (13.5…”
Section: Neutral Turbulence Generated Irregularitiesmentioning
confidence: 99%